مقارنة بين الأداء الشرعي للدية وشركات التأمين (شركة ليبيا للتأمين أنموذجًا): Comparative Analysis of the Sharia Implementation of Diyya and Insurance Companies: A Case Study of Libya Insurance Company - Elbalazi, Samira Hasan; Mohamed Razi, Nor Fahimah; Abdul Khalil, Shahidra (International Journal of Al-Turath In Islamic Wealth and Finance, 2025)
الملخص تناولت الدراسة أداء شركة ليبيا للتأمين وهي شخص قانوني أمام القضاء والمحاكم الليبية ، تعد المسألة من النوازل الفقهية المعاصرة المهمة لكثرت حوادث السيارات وما ينتج عنها ، تمت المقارنة بين الأداء الشرعي للعاقلة وأداء شركة ليبيا للتأمين لدية الخطأ الناجمة عن حوادث السيارات، استخدمت الباحثة المنهج الاستقرائي والمنهج التحليلي والاستعانة بالمنهج المقارن للوصول إلى جوانب الاختلاف، اتضح اختلاف أداء شركة التأمين عن الأداء الشرعي للعاقلة من حيث المدة والكيفية والشروط والصلاحية والعموم والشرعية والأداء، بينت الدراسة أن عدم تأمين السيارة لا يسقط الدية الواجبة على الجاني، عدم التعمد لا يعفي من الضمان، تم اقتراح إنشاء شركات تأمين إسلامية لمعالجة الأضرار الناجمة عن حوادث السير. Abstract This study examines the performance of Libya Insurance Company, as a legal entity before the Libyan judiciary and courts. The issue represents an important contemporary jurisprudential matter due to the increasing number of car accidents and their resulting consequences. A comparison was made between the Sharia-based role of al-‘Aqilah and the role of Libya Insurance Company in compensating for unintentional car accident damages. The researcher employed the inductive method, the analytical method, and the comparative method to identify areas of divergence. The findings revealed differences between the practices of insurance companies and the Sharia-based role of al-‘Aqilah in terms of duration, procedures, conditions, validity, scope, legitimacy, and execution. The study further emphasized that the absence of car insurance does not exempt the perpetrator from the obligation of Diyya, and that lack of intent does not remove liability. Finally, the study recommends the establishment of Islamic insurance companies to address damages arising from traffic accidents.